NF-κB/AP-1-Targeted Inhibition of Macrophage-Mediated Inflammatory Responses by Depigmenting Compound AP736 Derived from Natural 1, 3-Diphenylpropane Skeleton. (20th October 2014) - Ha, Van Thai; Beak, Heung Soo; Kim, Eunji; Baek, Kwang-Soo; Hossen, Muhammad Jahangir; Yang, Woo Seok; Kim, Yong; Kim, Jun Ho; Yang, Sungjae; Kim, Jeong-Hwan; Joo, Yung Hyup; Lee, Chang Seok; et al.
Abstract : AP736 was identified as an antimelanogenic drug that can be used for the prevention of melasma, freckles, and dark spots in skin by acting as a suppressor of melanin synthesis and tyrosinase expression. Since macrophage-mediated inflammatory responses are critical for skin health, here we investigated the potential anti-inflammatory activity of AP736. The effects of AP736 on various inflammatory events such as nitric oxide (NO)/prostaglandin (PG) E2 production, inflammatory gene expression, phagocytic uptake, and morphological changes were examined in RAW264.7 cells. AP736 was found to strongly inhibit the production of both NO and PGE2 in lipopolysaccharide- (LPS-) treated RAW264.7 cells. In addition, AP736 strongly inhibited both LPS-induced morphological changes and FITC-dextran-induced phagocytic uptake. Furthermore, AP736 also downregulated the expression of multiple inflammatory genes, such as inducible NO synthase (iNOS), cyclooxygenase- (COX-) 2, and interleukin- (IL-) 1 β in LPS-treated RAW264.7 cells. Transcription factor analysis, including upstream signalling events, revealed that both NF- κ B and AP-1 were targeted by AP736 via inhibition of the IKK/I κ B α and IRAK1/TAK1 pathways. Therefore, our results strongly suggest that AP736 is a potential anti-inflammatory drug due to its suppression of NF- κ B-IKK/I κ B α and AP-1-IRAK1/TAK1 signalling, which may make AP736 useful for the treatment of macrophage-mediated skin inflammation.